2021
DOI: 10.3389/fmicb.2021.653595
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and Clonal Spread of CTX-M-65-Producing Escherichia coli From Retail Meat in Portugal

Abstract: The emergence and dissemination of resistance to third- and fourth-generation cephalosporins among Enterobacteriaceae from different sources impose a global public health threat. Here, we characterized by whole-genome sequencing four Escherichia coli strains harboring the blaCTX–M–65 gene identified among 49 isolates from beef and pork collected at retail. The genomic content was determined using the Center for Genomic Epidemiology web tools. Additionally, the prediction and reconstruction of plasmids were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…The link between antimicrobial use and resistance is complex, but the emergence of resistance is likely to be specific to each drug and to each microorganism [ 34 ]. Therefore, horizontal gene transfer and clonal expansion are giving rise to highly resistant microorganisms [ 5 , 35 ]. Nevertheless, other factors, such as cross-selection and co-selection, are highly pertinent while addressing antibiotic resistance [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The link between antimicrobial use and resistance is complex, but the emergence of resistance is likely to be specific to each drug and to each microorganism [ 34 ]. Therefore, horizontal gene transfer and clonal expansion are giving rise to highly resistant microorganisms [ 5 , 35 ]. Nevertheless, other factors, such as cross-selection and co-selection, are highly pertinent while addressing antibiotic resistance [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic platform analysis revealed that the bla CTX–M gene was flanked by Tn2-like transposase and ISEcp1 downstream and upstream in both genetic environments, respectively. IS Ecp1 , belonging to the IS 1380 family, is one of the most important insertion sequences associated with bla CTX–M genes ( Zhao and Hu, 2013 ; Leão et al, 2021 ). Tn3 transposon, which is conjugative, was also detected.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was identified in four isolates, three from beef and one from pork. Genomic characterization by whole genome sequencing and genetic relatedness with other E. coli genomes suggest a clonal spread in Europe [ 72 ]. This enzyme is widely distributed in the Asian and North and South American continents [ 73 , 74 , 75 , 76 ], and only scarce studies reported its presence in Europe in humans, animals, and food [ 47 , 71 , 77 , 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 89 resistant isolates with a wide range of MICs (0.25 to ≥8 mg/L), PMQR were detected in 52, being qnrB the most frequent ( n = 27), followed by qnrS ( n = 21) and aac(6′)-Ib-cr ( n = 4), in agreement with other studies [ 20 ]. Of note, the four CTX-M-65 producers co-harbored qnrS and aac(6′)-Ib-cr [ 72 ]. Studies in China in Enterobacteriaceae ESBL producers identified strains co-harboring two and three PMQR-encoding mechanisms simultaneously [ 76 , 101 ].…”
Section: Discussionmentioning
confidence: 99%